Bird strike in aviation : statistics, analysis and management - El-Sayed, Ahmed F. (John Wiley & Sons, Ltd, 2019)
Groundbreaking Handbook Offers Detailed Research and Valuable Methodology to Address Dangerous and Costly Aviation Hazard Though annual damages from bird and bat collisions with aircraft have been estimated at $400 million in the United States and up to $1.2 billion in commercial aviation worldwide and despite numerous conferences and councils dedicated to the issue, very little has been published on this expensive and sometimes-lethal flying risk. Bird Strike in Aviation seeks to fill this gap, providing a comprehensive guide to preventing and minimizing damage caused by bird strike on aircraft. Based on a thorough and comprehensive examination of the subject, Dr. El-Sayed offers different approaches to reducing bird strikes, including detailed coverage of the three categories necessary for such reduction, namely, awareness/education, bird management (active and passive control), and aircraft design. In addition, the text discusses the importance of cooperation between airplanes, airports and air traffic authorities as well as testing methods necessary for certification of both aircraft frame and engine. Other notable features include: -Statistics and analyses for bird strikes with both civil and military helicopters as well as military fixed wing aircrafts, including annual costs, critical flight altitudes, critical parts of aircraft, distance from air base and specifics of date and timing -Thorough review and analysis all fatal bird strike accidents and most non-fatal accidents since 1905, the first book to provide such a reference -The use of numerical methods in analyzing historic data (ex. probability functions, finite element methods for analyzing impact on aircraft structure, experimental measurement technique for displacement, vibration, component distortion, etc.) -Instruction on identification of bird species (using visual, microscopic, and DNA evidence) and details of bird migration to aid air traffic control in avoiding scenarios likely to result in collision With its wealth of statistical data, innovative research, and practical suggestions, Bird Strike in Aviation will prove a vital resource for researchers, engineers and graduate students in aerospace engineering/manufacturing or ornithology, as well as for military and civilian pilots and flight crew or professionals in aviation authorities and air traffic control.